Performance-enhancing substance use and criminal offending: A 15-year prospective cohort study. (1st September 2021) - Ganson, Kyle T.; Testa, Alexander; Jackson, Dylan B.; Nagata, Jason M.
Highlights: Performance-enhancing substance use is associated with criminal offending. The association persisted at both seven- and 15-year follow up. These results expand prior research on steroid use and criminal activity. Abstract: Background: Research has documented an association between anabolic-androgenic steroid (AAS) use and criminal offending. Still, whether legal performance-enhancing substance (e.g., creatine; PES) use is similarly associated with criminal offending is unknown. The aim of the present study was to determine the prospective associations between legal PES use and AAS use and criminal offending among U.S. adults. Methods: Data from three waves over 15 years of the National Longitudinal Study of Adolescent to Adult Health, a prospective cohort study, were analyzed. Legal PES use and AAS use were assessed at Wave III (ages 18−26) and criminal offending was assessed at Wave IV (ages 24−32; N = 10, 861) and Wave V (ages 33–43; N = 9, 451). Criminal offending was measured using a summed score of six items (range 0–6). Multiple negative binominal regressions were conducted, transformed to incident rate ratios (IRR), adjusting for biological sex, age, race/ethnicity, household income, body mass index, depression, smoking, alcohol, and prior victimization and offending. Main Findings: Among the sample (51.3 % male; 68.8 % White), legal PES use (Wave IV: IRR 1.46, 95 % confidence interval [CI] 1.15−1.85; Wave V: IRR 1.52, 95 % CI 1.02−2.27) and AAS use (Wave IV: IRR 1.73, 95 % CI 1.09−2.76; Wave V: IRR 2.36, 95 % CI 1.33−4.19) were prospectively associated with criminal offending during young and middle adulthood, while adjusting for demographic and behavioral factors. Conclusions: These results confirm and expand upon prior research by describing the prospective associations between both legal PES use and AAS use and criminal offending among a nationally representative sample of U.S. adults.